تأثير التغيرات المناخية على الفواقد المائية أثناء الرش (Latakia University Journal -Engineering Sciences Series, 2019)
Reducing the water losses from irrigation system is important for achieving water conservation. The effect of monthly and daily climate variations on water losses due to evaporation and wind drift during sprinkling have been investigated experimentally. Three types of sprinklers were used in this research: Al-khirat, Andlian and Rainbird40. For Al-khirat sprinkler and during irrigation season, the maximum water losses occur in August (50%), while the minimum water losses occur in May (27%). For July, the measurements showed that the water losses during daytimes were 2.5 to 3.4 times the water losses during nighttimes. The comparison between experimental and Frost and Schwalen nomograph results showed that the experimental results were always higher than the Frost and Schwalen results. إن تخفيض الضياعات المائية في أنظمة الري له أهمية كبيرة في المحافظة على المياه. لقد تم في هذا البحث تحديد تأثير التغيرات المناخية اليومية والشهرية على الضياعات المائية نتيجة للتبخر وجرف الهواء أثناء الرش بشكل تجريبي. واستخدام لذلك ثلاثة أنواع من المرشات هي مرش الخيرات ومرش أندليان ومرش Rainbird40 . وإن دراسة الضياعات بالتبخر وجرف الهواء خلال موسم السقاية لدى استخدام مرش الخيرات أظهرت أن أكبر الضياعات حدثت خلال شهر آب 50% وأقل ضياعات حدثت خلال شهر أيار 27%. كما أن دراسة تغير الضياعات في اليوم خلال شهر تموز أظهرت أن الضياعات من الرش أثناء النهار تراوحت بين 2.5 و 3.0 مرات قيمة الضياعات أثناء الرش في ساعات الليل. وبمقارنة الضياعات المحسوبة بواسطة مخطط فروست وسكوالين مع القيم المقاسة لها، تبين أن الضياعات المقاسة أكبر بشكل واضح من الضياعات المستنتجة باستخدام هذا المخطط.